End-to-end networks vs named data network: A critical evaluation - Hassan, Suhaidi; Elbreiki, Walid; Firdhous, Mohamed; Monzer Habbal, Adib M. (Penerbit UTM Press, 2015)
Named data networking or information centric networking is the newest networking paradigm that gives foremost place to the contents in identification and dissemination.On the other hand, the end to end networking paradigm on which the Internet is currently built on places heavy emphasis on devices that make the architecture. The current Internet suffers from many shortcomings due to the misplaced emphasis. In order to overcome some of these deficiencies, researchers and developers have come up with patches and work around that have made the Internet more complex than it ought to be. Named data networking is a clean slate approach in building a network architecture overcoming all the current deficiencies and make it future safe. Several researchers have carried out comparative studies between named data networking and end to end networking. But these studies concentrate only on the features and capabilities of the networking paradigms. This is the first attempt at quantifying the performance the networking architectures experimentally. The authors in this paper present the results of the comparative study carried out experimentally in a simulated environment based on the final throughput. The results have been presented in a graphical form for easy visualization of results.